Design development and performance evaluation of photovoltaic/thermal (PV/T) hybrid solar dryer for drying of ber (Zizyphus mauritiana) fruit. Issue 1 (1st January 2018) - Poonia, Surendra; Singh, A.K.; Jain, Dilip
Abstract: This research paper describes the drying kinetics of ber ( Zizyphus mauritiana) fruit and economic evaluation of hybrid photovoltaic/thermal (PV/T) solar dryer fabricated using locally available materials, e.g. galvanized iron sheet, glass, PV panel and fan. Ber fruits were dried to the safe level moisture content (20%) in a period of 240 h with the drying load of 18 kg. Four mathematical models were evaluated to predict the behaviour of ber (Zizyphus mauritiana) drying in a combined hybrid PV/T solar dryer. Experimental data of moisture ratio (MR) and temperature obtained from dryer were fitted to the four empirical drying models. The performance of the drying model was compared based on their statistical parameters: coefficient of determination (R 2 ), root mean square error (RMSE) and reduced chi-square (χ 2 ) between the observed and predicted MR. The logarithmic model was found to be the most suitable for describing the thin layer drying behaviour of ber ( Zizyphus mauritiana) . The effective moisture diffusivity was 3.34 × 10 −7  m 2 /s and the efficiency of this dryer was found to be 16.7%. The developed hybrid PV/T drying system produces better quality products in shorter time by the efficient use of solar energy. The economic evaluation of the hybrid photovoltaic thermal (PV/T) solar dryer revealed that high value of IRR (54.5%) and low value of payback period (2.26 Years) make the dryer unit cost-efficient ensuring its economic viability.